Mindfulness, Stress, and Coping Among University Students - Palmer, Angèle; Rodger, Susan (Canadian Journal of Counselling and Psychotherapy, 2009)
A sample of 135 first-year university students living in residence completed questionnaires that measure individual differences in mindfulness, coping styles, and perceived stress. Findings revealed significant positive relationships between mindfulness and rational coping, and significant negative relationships with emotional and avoidant coping and perceived stress. Regression analyses revealed that avoidant coping and perceived stress predicted 38.2% of the variance of mindfulness scores. Findings from this study improve our understanding of how mindfulness relates to coping styles, thereby suggesting potential ways to enhance counselling service and programming for first-year university students during the often difficult transition to university.